2006
DOI: 10.1515/jpem.2006.19.8.963
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Central Precocious Puberty with Triptorelin 11.25 mg Depot Formulation

Abstract: A new triptorelin 11.25 mg long depot formulation is now available for the treatment of central precocious puberty (CPP). The aim of our study was to evaluate the efficacy of triptorelin 11.25 mg administered every 90 days to suppress gonadotropin and sex steroid secretion and pubertal signs in children with CPP during 2 years of treatment. Inclusion criteria were clinical pubertal development before the age of 8 years in girls or 9 years in boys, advanced bone age and a pubertal LH response (peak >5 mIU/ml) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…In short-term trials, quarterly triptorelin demonstrated its efficacy in suppressing gonadotropin secretion to prepubertal levels in the large majority of treated children [8,9,10]. In addition, we reported that triptorelin 11.25 mg was able to suppress LH peak during a standard GnRH test to a similar extent as the 3.75 mg formulation at 3 and 6 months of follow-up [18], suggesting that the two triptorelin preparations are likely equivalent, at least in terms of gonadotropin suppression in girls with CPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In short-term trials, quarterly triptorelin demonstrated its efficacy in suppressing gonadotropin secretion to prepubertal levels in the large majority of treated children [8,9,10]. In addition, we reported that triptorelin 11.25 mg was able to suppress LH peak during a standard GnRH test to a similar extent as the 3.75 mg formulation at 3 and 6 months of follow-up [18], suggesting that the two triptorelin preparations are likely equivalent, at least in terms of gonadotropin suppression in girls with CPP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we reported that triptorelin 11.25 mg was able to suppress LH peak during a standard GnRH test to a similar extent as the 3.75 mg formulation at 3 and 6 months of follow-up [18], suggesting that the two triptorelin preparations are likely equivalent, at least in terms of gonadotropin suppression in girls with CPP. However, these trials were limited to 6-24 months of follow-up [8,9,10,19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children recruited to the studies analysed in the meta-analysis met the following criteria: proven CPP defined as onset of sex characteristics development before the age of 8 years in girls and 9 years in boys based on the Tanner criteria consensus statement definition [1-3], with a pubertal response of LH to LH-releasing hormone in both sexes (stimulated LH >5 IU/L in Martinez-Aguayo et al [10] and Zenaty et al [11]; >6 IU/L in Bertelloni et al [8] or >7 IU/L in Carel et al [4] and Chiocca et al [9]), and a bone age >1 year ahead of the chronological age. As this was a retrospective study, no further ethical approval was sought beyond that obtained for all patients in the original studies.…”
Section: Methodsmentioning
confidence: 99%
“…Correct diagnosis of the etiology of sexual precocity is critical, because treatment of patients with PPP is different from those with CPP, and some PPP can secondarily evolve into CPP (6). Standard treatment of CPP is to suppress the activation of HPGA (7) through periodically using GnRH agonists such as leuprorelin depot (8) and triptorelin depot (9,10). Patients with CPP have to continue receiving this medication until they reach the average age of the onset of puberty.…”
mentioning
confidence: 99%